Aerosol and snow transfer processes: An investigation on the behavior of water-soluble organic compounds and ionic species. (September 2017) - Barbaro, Elena; Zangrando, Roberta; Padoan, Sara; Karroca, Ornela; Toscano, Giuseppa; Cairns, Warren R.L.; Barbante, Carlo; Gambaro, Andrea
Abstract: The concentrations of water-soluble compounds (ions, carboxylic acids, amino acids, sugars, phenolic compounds) in aerosol and snow have been determined at the coastal Italian base "Mario Zucchelli" (Antarctica) during the 2014–2015 austral summer. The main aim of this research was to investigate the air-snow transfer processes of a number of classes of chemical compounds and investigate their potential as tracers for specific sources. The composition and particle size distribution of Antarctic aerosol was measured, and water-soluble compounds accounted for 66% of the PM10 total mass concentration. The major ions Na +, Mg 2+, Cl − and SO4 2− made up 99% of the total water soluble compound concentration indicating that sea spray input was the main source of aerosol. These ionic species were found mainly in the coarse fraction of the aerosol resulting in enhanced deposition, as reflected by the snow composition. Biogenic sources were identified using chemical markers such as carboxylic acids, amino acids, sugars and phenolic compounds. This study describes the first characterization of amino acids and sugar concentrations in surface snow. High concentrations of amino acids were found after a snowfall event, their presence is probably due to the degradation of biological material scavenged during the snow event. Alcohol sugars increased in concentration after the snow event, suggesting a deposition of primary biological particles, such as airborne fungal spores. Highlights: The air-snow transfer processes were evaluated using water soluble compounds. This is the first study about amino acids and sugar concentration in surface snow. Water soluble organic fractions of Antarctic aerosol and snow were investigated.